Methodical bases of information support for complex analysis of system objects difficult/weakly structured - Kozulia, Tatyana Vladimirovna; Kozulia, Maria Mikhailovna (Premier Publishing s.r.o., 2020)
The complex methodological approaches for solving problem tasks objects quality assessment are determined on the basis of system analysis means com-bination and of the information and software complex development of research data processing with use of modern mean knowledge providing. Methodological support is based on theoretical knowledge in field of information entropy theory, synergetic, knowledge-oriented databases development; information space of integrating enti-ties unity principles. The scientific and practical foundations of methodological and informational support for the determination of complex systems state assessment and their functional capabilities, safety level of the investigated objects, using of knowledge-oriented information systems for obtaining knowledge on the research objects results at level “state (system –environment) – change – process – system state”. The generalized algorithmic approach from complex system object analysis as integrity having its mi-crostructure to which it is proposed to attribute not only component components and elements, but also processes of its functioning is developed. Practical implementation of the proposed informational and methodological approaches for complex systems study analysis on the entropy-information basis is shown on the results of quality and safety functioning assessment of natural-technological, ecological-economic systems, providing operational control and safety management of technological processes.
Keywords: environmental safety; methods of system analysis; mathematic modeling methods; information monitoring systems